Electrografting of sterically bulky tetramethylaniline groups on glassy carbon electrodes through aryldiazonium chemistry : reasons for the formation of multilayers - Subrata, Arnold (2022)
Within the field of electrografting with aryldiazonium cations, there are various methods available to graft a monolayer of organic groups onto electrode surfaces. One of these relies on the presence of steric groups or constraints on the aryldiazonium cation itself, which prevent multilayers from being formed by blocking access of the free aryl carbons on the grafted layer to the diazonium cations. Here, we investigate the nature of the layer formed from the electrochemical reduction of bulky 2,3,5,6-tetramethylaniline monodiazonium cations on glassy carbon (GC) electrodes, to form 2,3,5,6-tetramethylaniline-modified GC (GC−TMA), which was subsequently characterized by atomic force microscopy scratching, cyclic voltammetry, electrochemical impedance spectroscopy, and X-ray photoelectron spectroscopy. Despite the bulky structure of the TMA group, GC−TMA was found to exhibit sparse multilayers, owing to the ability of the precursor to undergo its own electropolymerization under the experimental conditions used.